2020
DOI: 10.1002/ange.201916681
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Water‐Splitting Photocatalysts by Loading with Ultrafine Rh–Cr Mixed‐Oxide Cocatalyst Nanoparticles

Abstract: The activity of many water-splitting photocatalysts could be improved by the use of Rh III -Cr III mixed oxide (Rh 2Àx Cr x O 3 )p articles as cocatalysts.A lthough further improvement of water-splitting activity could be achieved if the sizeo ft he Rh 2Àx Cr x O 3 particles was decreased further,i ti s difficult to load ultrafine (< 2nm) Rh 2Àx Cr x O 3 particles onto aphotocatalyst by using conventional loading methods.Inthis study,anew loading method was successfully established and was used to load Rh 2Àx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The values, compiled in Table S1 (Supporting Information), confirm that the prolongation of the MSD deposition times led to controlled increments of cocatalyst loadings on the photocatalysts, with very low contents that do not impair the function of the main absorber [21,22,36] …”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The values, compiled in Table S1 (Supporting Information), confirm that the prolongation of the MSD deposition times led to controlled increments of cocatalyst loadings on the photocatalysts, with very low contents that do not impair the function of the main absorber [21,22,36] …”
Section: Resultsmentioning
confidence: 69%
“…Since the focus of this investigation lies on the effects brought by bimetallic oxide cocatalysts on the photocatalytic water splitting activity of Fe 2 TiO 5 , we should consider some established assumptions: the ultra‐small cocatalyst nanoparticles must not block the light absorption by the main absorber and the distribution of these nanoparticles should be as homogeneous as possible to guarantee the achievement of the maximum rates for the redox reactions at the solid/liquid interface. This configuration is prone to turn the cocatalyst shell transparent for the incident solar light [21,36] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, in recent years, metal oxide, hydroxide, sulfide, phosphide, selenide, nitride, and other noble-metal alternative materials have been widely studied in the field of photocatalysis. 29,[133][134][135][136][137][138] Among these, due to the unique electronic structure of cobalt and the excellent electrical conductivity, abundant active sites, and corrosion resistance, cobalt-based nitrides have also been used as co-catalysts in photocatalytic reactions. For instance, Chen et al reported that cobalt nitride (Co 3 N) can be used as an efficient co-catalyst on CdS nanorods (CdS NRs) for photocatalytic hydrogen production under visible light irradiation.…”
Section: Cobalt-based Nitrides As Photocatalytic Co-catalystsmentioning
confidence: 99%
“…Additionally, photoinduced surface modification by generating reactive species on the Bi 4 TaO 8 Cl surface was also reported [36]. Despite most the of literatures having demonstrated improved photocatalytic activities on Bi 4 TaO 8 Cl through surface modification [37], or loading of -suitable cocatalyst [38], the relationship between the intrinsic photoreactivity and the exposed facets is still unclear, and there is a lack of in-depth exploration about the crystal facet-dependent charge separation properties of Bi 4 TaO 8 Cl.…”
Section: Introductionmentioning
confidence: 99%